2016
DOI: 10.1590/1516-4446-2015-1681
|View full text |Cite
|
Sign up to set email alerts
|

Depression, quality of life, and body composition in patients with end-stage renal disease: a cohort study

Abstract: Objective: To prospectively evaluate depressive symptoms, nutritional status, and quality of life (QoL) and search for possible associations in patients with end-stage renal disease undergoing hemodialysis. Methods: A cohort study of 104 adult patients with end-stage renal disease undergoing hemodialysis was conducted. Anthropometric, clinical, and biochemical variables were evaluated after a midweek hemodialysis session. The participants' body composition was assessed by direct segmental multifrequency bioimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…Negative correlations between emotional disorders and quality of life domains have been widely reported. [14][15][18][19][20][21][22] Perales Montilla et al 41 compared the capacity of self-reported somatic symptoms and depression and anxiety for predicting quality of life among patients with chronic renal disease. Their results indicated that mood was a predictor of reductions in the physical and mental components of the SF-36, compared with the number and severity of physical symptoms.…”
Section: Severity Of Depression and Anxiety Symptomsmentioning
confidence: 99%
“…Negative correlations between emotional disorders and quality of life domains have been widely reported. [14][15][18][19][20][21][22] Perales Montilla et al 41 compared the capacity of self-reported somatic symptoms and depression and anxiety for predicting quality of life among patients with chronic renal disease. Their results indicated that mood was a predictor of reductions in the physical and mental components of the SF-36, compared with the number and severity of physical symptoms.…”
Section: Severity Of Depression and Anxiety Symptomsmentioning
confidence: 99%
“…In dialysis patients, insufficient nutritional intake, compromised clinical well-being, comorbidity and dialysis related factors can lead to poor nutritional status [4][5][6]. Poor nutritional status is on its turn associated with impaired functional capacity, increased risk of complications, lower quality of life and limited survival [3,[7][8][9]. Therefore it seems important to identify patients at risk for malnutrition already at an early stage, in order to start interventions to improve their nutritional status and clinical and mental outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between inflammation, malnutrition, and depression has been previously proposed [ 9 13 ]. However, our study did not identify any impact of BMI, serum Alb, Hb, TC, or TG on depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that economic and social factors are associated with depression and health-related QoL in patients with CKD [ 8 ]. Other studies have found that nutrition and inflammation also impact psychological disorders in patients with CKD and other patient populations [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%